2015
DOI: 10.1016/j.fsigss.2015.09.034
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the reliability of the data generated by Next Generation Sequencing from artificially degraded DNA samples

Abstract: NGS has the potential to be a promising technology for recovering genetic information from challenging\ud specimens in forensic genetics. In order to understand the role of DNA damage on the outcome of NGS, we\ud investigated the performance of ForenSeqTM DNA Signature kit, Illumina (in its pre-commercial version)\ud on a set of in vitro degraded trial DNA samples. After DNA quantification by qPCR, duplicate analyses of\ud the samples were carried out. The resulting molecular products were then sequenced by us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 5 publications
(8 reference statements)
0
8
0
Order By: Relevance
“…As reported in Tables and , the analysis of STR and SNP data showed a high percentage of loci which gave none or less than 50 reads in the three trial samples (up to 75.7–76.1% in sample FM‐10) and a positive trend between the extent of DNA degradation and the % of low‐covered loci. Although this setting of the cut‐off value is arbitrary, and leads to a loss of genetic information of up to 5.7% (when compared to the cut‐off of 30 x) , we believe that a conservative approach focused on the reliability of the results is what is needed in forensic genetics when validation studies are underway to better understand the potential of an innovative technique.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As reported in Tables and , the analysis of STR and SNP data showed a high percentage of loci which gave none or less than 50 reads in the three trial samples (up to 75.7–76.1% in sample FM‐10) and a positive trend between the extent of DNA degradation and the % of low‐covered loci. Although this setting of the cut‐off value is arbitrary, and leads to a loss of genetic information of up to 5.7% (when compared to the cut‐off of 30 x) , we believe that a conservative approach focused on the reliability of the results is what is needed in forensic genetics when validation studies are underway to better understand the potential of an innovative technique.…”
Section: Resultsmentioning
confidence: 99%
“…The only pivot study performed with the ForenSeq TM DNA Sequencing kit reported a minimum DoC of 10x . Our preliminary data analysis, performed with a cut off of 30x, evidenced mistyping error rates of up to 2.2% in these three trial samples . For this reason, we tried to reduce these error rates by increasing the minimum coverage for “locus call” to 50x.…”
Section: Methodsmentioning
confidence: 92%
“…Reliable and reproducible results were produced from high-concentration single-source samples and profiles could be differentiated from mixed samples (Churchill et al, 2016;Iozzi et al, 2015). Low concentration, degraded and case type samples produced results concordant with CE data (Carboni et al, 2015;Churchill et al, 2016). The BGA and EVC SNPs were also tested and found to accurately predict the ancestry, hair and eye color of European and East Asian samples (Hussing, Borsting, Mogensen, & Morling, 2015).…”
Section: The Miseq Fgx™ Forensic Genomics Solutionmentioning
confidence: 90%
“…After a number of studies completed assessments of the MFGS (Caratti, Turrina, Ferrian, Cosentino, & De Leo, 2015;Carboni et al, 2015;Churchill et al, 2016;Hussing et al, 2015;Iozzi et al, 2015;Just, Moreno, Smerick, & Irwin, 2017), Jäger et al (2017) published the developmental validation of the MFGS. Since then others have completed internal and inter laboratory studies (Köcher et al, 2018;Laurent et al, 2017;Moreno et al, 2018).…”
Section: Validationmentioning
confidence: 99%
“…Moreover, since the DNA fragments do not have to be separated by size, the amplicon length can be reduced, which benefits the analysis of degraded samples [1,19]. Additionally, the sequencing of SNPs can provide valuable information if CE-based STR typing fails [4].…”
Section: Introductionmentioning
confidence: 99%